2010
DOI: 10.1002/ccd.22243
|View full text |Cite
|
Sign up to set email alerts
|

Results of percutaneous drug‐eluting stent implantation for unprotected left main coronary disease according to left ventricular systolic function

Abstract: Systolic ventricular dysfunction is highly correlated with in-hospital and long term death rates in patients undergoing PCI with DES for ULM disease. However it does not confer an increased risk of nonfatal adverse events or stent thrombosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Although previous studies have shown that HF is associated with more cardiac death in patients after coronary stenting, 37 and a lower LVEF predicts MACE after PCI for ULMCA stenosis, 38 HF is never shown to associate with more TLR. Multiple analyses in this retrospective study having a small number of events may increase the chance of false-positive findings, and a wide range of confidence interval may suggest this possibility.…”
Section: Hf and Outcomes Following Pci For Distal Ulmca Stenosismentioning
confidence: 87%
“…Although previous studies have shown that HF is associated with more cardiac death in patients after coronary stenting, 37 and a lower LVEF predicts MACE after PCI for ULMCA stenosis, 38 HF is never shown to associate with more TLR. Multiple analyses in this retrospective study having a small number of events may increase the chance of false-positive findings, and a wide range of confidence interval may suggest this possibility.…”
Section: Hf and Outcomes Following Pci For Distal Ulmca Stenosismentioning
confidence: 87%
“…In that registry, the median survival in patients with preserved left ventricular function between CABG and medical therapy was similar ( P = 0.94), but there were significant differences in median survival with mild left ventricular dysfunction ( P = 0.01) and with severe left ventricular dysfunction ( P < 0.001). Bollati et al [8] reported that poor left ventricular function significantly increased the risk of overall mortality ( P < 0.001) and cardiac mortality ( P = 0.001) in patients with DES for ULMCA stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of left ventricular dysfunction is a predictor of survival in patients with ULMCA disease [3, 7]. Patients with normal ejection fraction have significantly improved outcomes compared with patients with low ejection fraction, but these studies followed up patients for less than 2 years [8, 9]. Long‐term outcomes of patients with normal left ventricular function who underwent ULMCA PCI with bare‐metal stents were associated with low cardiac mortality but relatively high rates of target lesion revascularization (TLR; 16.7%) at a follow‐up of 3 years [9].…”
Section: Introductionmentioning
confidence: 99%